Nilai Pendidikan Karakter Tokoh Sri Ningsih dalam Novel “Tentang Kamu” Karya Tere Liye - Alya Hafizha (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research was conducted to increase the value of character education in children through written literary works, especially the novel entitled